2019
DOI: 10.1177/0971333618825051
|View full text |Cite
|
Sign up to set email alerts
|

Caste-based Oppression, Trauma and Collective Victimhood in Erstwhile South India: The Collective Therapeutic Potential of Theyyam

Abstract: The decades of collective victimhood and trauma that the oppressed lower caste members in the southern state of India (Kerala) suffered in silence were less known to the world until the socio-religious reform movements offered a space for their collective expression of agitation and unrest. With no socially sanctioned channels to express their injustice and pain, the folk ritual of Theyyam often became the alternative for a cathartic release of transgenerational and collective victimhood and trauma long endure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Asian Indians have culturally-rooted beliefs about what constitutes a trauma and what causes posttrauma distress; some of these beliefs match Western-based definitions and interpretations. Beyond the traumatic experiences already discussed, Asian Indians attribute the onset or exacerbation of posttrauma distress to additional stressors such as poor physical health, death or disappearance of loved ones, interpersonal problems including family conflicts, collective trauma for lower-caste individuals, immigration-related traumas, lack of basic and financial resources, value-action gap (e.g., engaging in behaviors counter to cultural values such as promiscuity), and lack of academic and professional achievement (Ahammed, 2019; Daga et al, 2020; A. Gilmoor et al, 2020; Housen et al, 2019).…”
Section: Socio-cultural Considerations For Culturally-adapted Posttra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Asian Indians have culturally-rooted beliefs about what constitutes a trauma and what causes posttrauma distress; some of these beliefs match Western-based definitions and interpretations. Beyond the traumatic experiences already discussed, Asian Indians attribute the onset or exacerbation of posttrauma distress to additional stressors such as poor physical health, death or disappearance of loved ones, interpersonal problems including family conflicts, collective trauma for lower-caste individuals, immigration-related traumas, lack of basic and financial resources, value-action gap (e.g., engaging in behaviors counter to cultural values such as promiscuity), and lack of academic and professional achievement (Ahammed, 2019; Daga et al, 2020; A. Gilmoor et al, 2020; Housen et al, 2019).…”
Section: Socio-cultural Considerations For Culturally-adapted Posttra...mentioning
confidence: 99%
“…Asian Indians may also prefer a holistic therapeutic approach for PTSD that adheres to a broader definition of wellness incorporating emotional, spiritual, and physical well-being (Asnaani et al, in press) given the collectivistic nature and religious/spiritual orientation of this community. This holistic approach may include indigenous treatments (yoga), local/communal rituals, Ayurvedic practices, prayer, or seeking help from spiritual healers (Agger et al, 2012; Ahammed, 2019; Housen et al, 2019; Pillaia et al, 2015; Tewary, 2005). Indeed, a study on psychiatric inpatients in India found that 75% of patients sought faith-healing rituals before seeking medical help and found these rituals to be beneficial (Kar, 2008).…”
Section: Socio-cultural Considerations For Culturally-adapted Posttra...mentioning
confidence: 99%
“…In the present study, close to two thirds of the participants (71% to be precise) belonged to the schedule caste community, and this is a reflection of the uneven distribution of wealth in India [66]. The mental health outcomes of lower caste communities in themselves bring forward staggering results that warrant a community-sensitive approach, taking into account the years of collective trauma [67]. For women, this represents a gendered vulnerability to violence and lower mental health well-being, owing to class and castebased inequalities [32,68] For instance, Prost et al (2012) found that women belonging to schedule tribes or schedule caste backgrounds reported higher psychological stress than higher-caste women [69].…”
Section: Risk Factorsmentioning
confidence: 58%
“…With approximately 35 million women "missing," India has one of the lowest sex ratios in the world. Indian women face outdated and repressive governance structures, an inefficient legal justice system, weak law enforcement, and male-dominated sociopolitical structures (Ahammed, 2019;Anderson & Ray, 2015;Reardon, 1985). Kandasamy's text illustrates the incidents of Tranquebar reeling from the shock of witnessing the sixty-fifth rape in three weeks, the landlords' gang rape of a fourteen-year-old girl, Thangamma, a pregnant woman pummeled by a gang of twenty armed men, and Anju being brutally beaten and torn apart her red blouse, which symbolizes communism and burns it in front of everyone, and Veerapan's young daughter, traumatized by rape, stopped speaking for no apparent reason, women struggle to make a meal out of scraps.…”
Section: The Gender Aspect Of Structural Violencementioning
confidence: 99%